Preparation method of CuZnAlGa hydrotalcite-like derivative catalyst for preparing methanol from carbon dioxide-rich synthesis gas

By preparing CUZNALGA water -class water derivatives, the CU/Zno/Al2O3 catalysts were solved. The problem of active sites in the high -concentration CO2 environment, realized high -efficiency methanol synthesis and stability, reducing the roasting temperature and energy consumption.

CN119368190AActive Publication Date: 2025-01-28TIANJIN UNIV

Patent Information

Application Number
CN202411354809.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-28
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the existing Cu/ZnO/Al2O3 catalysts, in the synthesis gas with high concentration of CO2, CO molecules compete for the adsorption active sites, affecting the yield of methanol, and the high-temperature roasting and passivation process consumes energy and is inconvenient to use.

Method used

The preparation method of CUZNALGA -type water stones derivatives is used to prepare catalysts with a layered skeleton structure, multi -active center, and high active sites through steps such as sedimentation, separation, drying, high temperature roasting and reducing.

Benefits of technology

This catalyst has significantly improved the catalytic activity and stability of methanol in the synthesis gas of carbon dioxide, realized efficient carbon resource conversion and utilization, and reduced the roasting temperature and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368190A_ABST
    Figure CN119368190A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a CuZnAlGa hydrotalcite-like derivative catalyst for preparing methanol from synthesis gas rich in carbon dioxide. Cu metal salt, Zn metal salt, Al metal salt and Ga metal salt are used as precursors, Na2CO3 and NaOH are used as precipitants, a mixed alcohol-water solution is used as an auxiliary solvent for coprecipitation, constant temperature and pH value are controlled, and a hydrotalcite-like structure catalyst precursor is obtained. And the precursor is subjected to high-temperature roasting and in-situ reduction in the hydrogen atmosphere, and then the layered framework structure with the Cu nano-particles fixed by the oxide is obtained. The hydrotalcite-like structure plays a role in crystal lattice confinement to prevent Cu particle aggregation, and the interaction between Cu and the oxide improves the adsorption capacity of the surface of the catalyst to CO and CO2, and enhances the activity and stability of methanol prepared from carbon dioxide-rich synthesis gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a method for preparing a CuZnAlGa-based hydrotalcite-derived catalyst for preparing methanol from carbon dioxide-rich synthesis gas. Background Art

[0002] With the growth of the world's population, the needs of industry and life have caused excessive emissions of carbon dioxide, leading to global climate change and seriously threatening the normal production and life of human beings. Methanol, as a low-carbon clean energy, can replace oil and gas, alleviate the dependence on oil and natural gas, and can also be used as a raw material to produce high-value chemicals. Traditional methanol production mainly adopts the CO-rich synthesis gas route (CO, CO2, H2). Increasing the CO2 content in the synthesis gas to form CO2-rich synthesis gas to produce methanol can effectively utilize CO2 resources. However, the mainstream Cu / ZnO / Al2O3 catalyst in the industry is limited by the CO2 content in this application. In the synthesis gas with high concentration of CO2, CO molecules and CO2 molecules compete for adsorption active sites, affecting the yield of methanol. Therefore, there are many studies on the modification of Cu / ZnO / Al2O3 catalyst by introducing additives. The introduced components are mostly one or more of metal oxides such as MgO, La2O3, CeO2, ZrO2, Ga2O3, SiO2, TiO2, etc. Since CO2 hydrogenation to methanol is a structure-sensitive reaction, in addition to the influence of catalytic components, the structure of the catalyst is also one of the important factors affecting catalytic activity.

[0003] CN104275185A discloses a copper-based hydrogenation catalyst that does not require reduction activation. The preparation process includes precipitation, aging, washing, filtering and aliphatic hydroxy acid reprocessing, and finally passivation in an oxidizing atmosphere after calcination in an inert atmosphere to obtain a preparation method for a Cu-based hydrogenation catalyst that does not require reduction activation. The CZAMg, CZALa, and CZAZrGa catalysts prepared by the method are respectively used in CO hydrogenation and CO2 hydrogenation to methanol. In a CO2-rich synthesis gas to methanol system, CO2 and CO molecules are hydrogenated at the same time, which will produce competitive adsorption on the catalyst surface, affecting the conversion efficiency of CO2 and CO reaction molecules. The catalyst prepared in this invention patent is applied to traditional synthesis gas to methanol and pure CO2 hydrogenation to methanol reactions and shows relatively excellent catalytic activity, but its catalytic performance in CO2-rich synthesis gas is not mentioned. In addition, the catalyst in this invention patent needs to be calcined at a temperature of more than 500°C, and then passivated under specific conditions and formed, which brings additional energy consumption and inconvenience to the catalyst use process.

[0004] CN109289854A discloses a high-stability and high-strength synthetic methanol catalyst and a preparation method thereof. The invention adopts a spray method to implement a two-step co-precipitation to prepare a methanol catalyst. Compared with other synthesis methods, this method significantly improves the catalyst reaction activity and thermal stability in CO hydrogenation to methanol. However, this method has certain requirements for the required spray equipment for preparing the catalyst, and the reaction uses a raw gas with a high hydrogen-to-carbon ratio. The concentration of CO2 in the raw gas is only 5%, and there is no obvious indication of the effect on the CO2 conversion rate, as well as the catalytic activity performance in high-concentration CO2 raw gas.

[0005] Therefore, designing and developing efficient Cu-based catalysts with multiple active centers suitable for producing methanol from CO2-rich syngas and their processes have important application value in realizing efficient conversion and utilization of carbon resources under mild reaction conditions. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a CuZnAlGa hydrotalcite-derived catalyst for preparing methanol from carbon dioxide-rich synthesis gas. The prepared catalyst has a layered skeleton structure, a large specific surface area, a complete crystal structure, a uniform particle size, a variety of active center types, and a high density of active sites, which is conducive to breaking through the limitation of CO2 content in synthesis gas to methanol, improving the catalytic activity and stability of methanol synthesis, and realizing efficient conversion and utilization of carbon resources.

[0007] The technical solution of the present invention to solve the technical problem is:

[0008] The present invention provides a method for preparing a CuZnAlGa-based hydrotalcite-derived catalyst for preparing methanol from carbon dioxide-rich synthesis gas, comprising the following steps:

[0009] 1) Coprecipitation: Weigh a certain amount of Cu salt, Zn salt, Al salt, and Ga salt and dissolve them in a mixed alcohol aqueous solution, and weigh a certain amount of precipitant and dissolve it in a mixed alcohol aqueous solution of the same concentration. The two solutions are simultaneously dripped into a four-necked flask drop by drop, accompanied by constant temperature hydrothermal and stirring and controlling a constant pH value. Continue stirring for 6-18 hours under certain hydrothermal conditions, stop stirring, and cool to room temperature.

[0010] 2) Separation: The precipitate from step 1) is separated by suction filtration, and the filter cake is washed with water and ethanol for multiple times to obtain a light blue precipitate in a colloidal state.

[0011] 3) Drying: Dry the light blue precipitate from step 2) in an oven.

[0012] 4) High-temperature calcination: The blue solid dried in step 3) is ground and then calcined at high temperature.

[0013] 5) Activation: The CuZnAlGa hydrotalcite-derived catalyst obtained in step 4) is reduced in a reducing gas atmosphere to obtain a CuZnAlGa catalyst with multiple active centers, which is composed of metal Cu nanoparticles and ZnO, Al2O3, and Ga2O3 metal oxides, maintains a layered skeleton structure, and has multiple active sites, wherein the mass ratio of (CuO+ZnO) to (Al2O3+Ga2O3) is (5-9):1, the mass ratio of CuO to ZnO is (2-5):1, and the mass ratio of Al2O3 to Ga2O3 is (1-9):1.

[0014] Furthermore, in step 1), the Cu salt, Zn salt, Al salt, and Ga salt are one or more of nitrates, acetates, halides, and sulfates.

[0015] Furthermore, the precipitant is one or more of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide and potassium hydroxide.

[0016] Furthermore, in step 1), the volume concentration of the mixed alcohol aqueous solution is 5-40%, and the mixed alcohol in the mixed alcohol aqueous solution is two or more of methanol, ethanol, n-propanol, n-butanol, ethylene glycol, and glycerol. Preferably, the mixed alcohol is a compound of methanol and ethylene glycol.

[0017] Furthermore, in step 1), a peristaltic pump is used to simultaneously drip the salt solution and the precipitant solution into the four-necked flask, and the rotation speed of the pump head is 5-30 rpm.

[0018] Furthermore, in step 1), mechanical stirring is used, and the rotation speed of the stirring blade is 600-1000 rpm.

[0019] Furthermore, in step 1), the hydrothermal condition is 30-60° C., the hydrothermal time is 6 h-18 h, and the constant pH range is controlled to be 8-10.

[0020] Furthermore, in step 2), the filter cake is washed with deionized water during the filtration process until the filtrate is neutral, and then washed once with ethanol.

[0021] Further, in step 3), the drying temperature is 60-100° C., and the drying time is 6-12 h.

[0022] Furthermore, in step 4), the calcination includes static calcination or flow atmosphere calcination, the calcination equipment includes a muffle furnace, a tubular furnace, and the calcination atmosphere is one or more of air, oxygen, nitrogen, and argon. The calcination temperature is 320-500°C, the calcination time is 4-6h, and the heating rate is 2-10°C / min.

[0023] Furthermore, in step 5), the catalyst is activated and reduced before use, the reducing atmosphere is hydrogen or a mixture of hydrogen and nitrogen (argon), the flow rate of the reducing gas is 2-20 mL / min, the reduction temperature is 250-300°C, the heating rate is 1-10°C / min, the pressure is normal pressure, and the reduction time is 1-4h.

[0024] The CuZnAlGa hydrotalcite-derived catalyst prepared by the invention is applied to the reaction of preparing methanol from carbon dioxide-rich synthesis gas.

[0025] Furthermore, the CuZnAlGa hydrotalcite-derived catalyst is used for the gas-solid fixed bed carbon dioxide-rich synthesis gas to methanol reaction, and the reaction conditions are: reaction pressure of 3-7MPa, reaction temperature of 180-280°C, reaction space velocity of 3000-18000mL / (g cat h), the raw gas is a synthesis gas rich in CO2, and further, the raw gas is a carbon-rich synthesis gas with a CO2 content of 20%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The CuZnAlGa hydrotalcite-derived catalyst provided by the present invention uses mixed alcohol as an auxiliary solvent to provide low surface tension and high OH - The system environment with high concentration of radicals makes the obtained hydrotalcite precursor have high crystallinity and complete structure. After catalyst reduction, the Cu particles have small particle size and uniform size.

[0028] 2. The CuZnAlGa hydrotalcite-derived catalyst provided by the present invention enhances the co-hydrogenation ability of CO2 and CO and improves the ability to catalyze the production of methanol from carbon dioxide-rich syngas by constructing the synergistic effect of multiple active centers at the Cu-ZnO interface and the Cu-Ga2O3 interface. Zn, Al, and Ga metal oxides tightly coat the Cu nanoparticles to increase the density of active sites. At the same time, the catalyst after calcination and reduction maintains the layered skeleton structure of the hydrotalcite-like catalyst, and the lattice confinement effect prevents the agglomeration of Cu particles.

[0029] 3. The CuZnAlGa hydrotalcite-derived catalyst of the present invention not only has high activity and high methanol selectivity, but more importantly, it also has high stability. The long-term stability evaluation results of the CuZnAlGa hydrotalcite-derived catalyst of the present invention at a reaction temperature of 240°C show that the CO2 conversion rate is always maintained at about 20% within a reaction time of 100 hours, and the CO conversion rate is always maintained at about 44%. The selectivity of CH3OH is stable at more than 99%. This shows that the CuZnAlGa hydrotalcite-derived catalyst has excellent activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1XRD patterns of CuZnAlGa-EM, CuZnAlGa-M, and CuZnAlGa-E hydrotalcite-derived catalyst precursors (LDH) prepared in Examples 1-3;

[0031] Figure 2 TEM images of CuZnAlGa-EM, CuZnAlGa-M, and CuZnAlGa-E hydrotalcite-derived catalysts prepared in Examples 1-3 after calcination and reduction;

[0032] Figure 3 Catalytic performance diagram of CuZnAlGa-EM, CuZnAlGa-M, and CuZnAlGa-E hydrotalcite-derived catalysts prepared in Examples 1-3;

[0033] Figure 4 TEM images of CuZnAl, CuZnAlGa, and CuZnGa hydrotalcite-derived catalyst precursors (LDH) prepared in Examples 14, 16, and 17 and after reduction;

[0034] Figure 5 The XRD patterns of CuZnAlGa hydrotalcite-derived catalyst precursors and calcined reductions with different CuO / ZnO ratios, where (a) is the XRD of the LDH precursor sample; (b) is the XRD of the sample after calcination; (c) is the XRD of the calcined sample after reduction;

[0035] Figure 6 The XRD patterns of CuZnAlGa hydrotalcite-derived catalyst precursors and calcined reductions with different Al2O3 / Ga2O3 ratios, where (a) is the XRD of the LDH precursor sample; (b) is the XRD of the sample after calcination; (c) is the XRD of the calcined sample after reduction;

[0036] Figure 7 The catalytic performance diagram of CuZnAlGa hydrotalcite-derived catalysts with different CuO / ZnO ratios, where (a) is the CO2 conversion rate; (b) is the CO conversion rate; (c) is the methanol space-time yield;

[0037] Figure 8 The catalytic performance diagram of CuZnAlGa hydrotalcite-derived catalysts with different Al2O3 / Ga2O3 ratios, where (a) is the CO2 conversion rate; (b) is the CO conversion rate; (c) is the methanol space-time yield;

[0038] Fig. 9 The catalytic performance diagram of CuZnAl, CuZnAlGa, and CuZnGa hydrotalcite-derived catalysts, where (a) is the CO2 conversion rate; (b) is the CO conversion rate; (c) is the methanol space-time yield;

[0039] Fig.10These are the results of long-term stability evaluation of CuZnAlGa hydrotalcite-derived catalysts at a reaction temperature of 240°C. DETAILED DESCRIPTION

[0040] The present invention is described below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The experimental methods for which specific conditions are not specified in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer, and the general equipment, materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial sources. The raw materials required in the following examples and comparative examples are all commercially available.

[0041] Examples 1-3 are preparations of CuZnAlGa catalysts using one alcohol and two alcohol solvents:

[0042] Example 1

[0043] Weigh 5.5g Cu(NO3)2·3H2O, 3.5g Zn(NO3)2·6H2O, 1.9g Al(NO3)3·9H2O, 0.8g Ga(NO3)2·3H2O in a 200mL beaker, add 80mL deionized water, 10ml methanol and 10mL ethylene glycol, and stir until dissolved. Weigh 0.83g Na2CO3 and 4g NaOH in a 300mL beaker, add 120mL deionized water, 15mL methanol and 15mL ethylene glycol, and stir until dissolved. Add 320mL deionized water, 40mL methanol and 40mL ethylene glycol to a 1L four-necked flask, accompanied by mechanical stirring at 600rpm. Use a peristaltic pump to add the prepared salt solution and alkaline solution dropwise to the four-necked flask at the same time, with a speed of 15rpm. The whole process maintains a hydrothermal condition of 40℃, pH=9.0±0.2. After the addition is complete, continue to maintain hydrothermal and stirring for 12 hours. After completion, filter and separate, rinse the filter cake with deionized water until the filtrate is neutral and then wash it once with ethanol. Dry in a 60°C oven for 12 hours. Grind the sky blue solid obtained in an agate mortar into powder. A certain amount of powder is placed in a muffle furnace and roasted in an air atmosphere with a heating rate of 4°C / min, a target temperature of 320°C, and maintained for 4 hours. The gray-green catalyst obtained after roasting is recorded as CZAG-EM. The catalyst is pressed into tablets (6MPa, 1min), crushed, and 40-60 mesh catalysts are screened for catalytic performance evaluation.

[0044] The prepared catalyst was evaluated using a fixed bed microreactor. First, 0.3 g of the screened catalyst was weighed and loaded into a reaction tube with an inner diameter of 8 mm. The catalyst was reduced in situ using 20 mL / min of pure H2, with a heating rate of 4 °C / min and a target temperature of 260 °C for 3 h. After the reduction was completed, a mixed gas of n(H2):n(CO2):n(CO):n(N2)=70:20:5:5 was used, 5 MPa, WHSV=6000 mL / (g cat h) The activity of the catalyst was evaluated at different temperatures under the following conditions.

[0045] Example 2

[0046] Weigh 5.5g Cu(NO3)2·3H2O, 3.5g Zn(NO3)2·6H2O, 1.9g Al(NO3)3·9H2O, 0.8g Ga(NO3)2·3H2O in a 200mL beaker, add 80mL deionized water and 20ml methanol, and stir until dissolved. Weigh 0.83g Na2CO3 and 4g NaOH in a 300mL beaker, add 120mL deionized water and 30ml methanol, and stir until dissolved. Add 320mL deionized water and 80mL methanol to a 1L four-necked flask, accompanied by mechanical stirring at a speed of 600rpm. The subsequent preparation and evaluation steps are the same as in Example 1, and the catalyst is recorded as CZAG-M.

[0047] Example 3

[0048] Weigh 5.5g Cu(NO3)2·3H2O, 3.5g Zn(NO3)2·6H2O, 1.9g Al(NO3)3·9H2O, 0.8g Ga(NO3)2·3H2O in a 200mL beaker, add 80mL deionized water and 20ml ethylene glycol, and stir until dissolved. Weigh 0.83g Na2CO3 and 4g NaOH in a 300mL beaker, add 120mL deionized water and 30ml ethylene glycol, and stir until dissolved. Add 320mL deionized water and 80mL ethylene glycol to a 1L four-necked flask, accompanied by mechanical stirring at a speed of 600rpm. The subsequent preparation and evaluation steps are the same as in Example 1, and the catalyst is recorded as CZAG-E.

[0049] Examples 4-9 are preparations of CuZnAlGa catalysts with different CuO / ZnO ratios:

[0050] Example 4

[0051] The metal salts used in the catalyst preparation were 5.215 g Cu(NO3)2·3H2O, 3.138 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, 0.615 g Ga(NO3)2·3H2O, 0.726 g Na2CO3 and 3.787 g NaOH as precipitants, and the obtained catalyst was recorded as C2Z1AG. The other preparation and evaluation steps were the same as those in Example 1.

[0052] Example 5

[0053] The metal salts used in the catalyst preparation were 5.588 g Cu(NO3)2·3H2O, 2.690 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, and 0.615 g Ga(NO3)2·3H2O. The precipitants used were 0.726 g Na2CO3 and 3.787 g NaOH. The obtained catalyst was recorded as C 2.5 Z1AG. Other preparation and evaluation steps are the same as those in Example 1.

[0054] Example 6

[0055] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, 0.615 g Ga(NO3)2·3H2O, 0.726 g Na2CO3 and 3.790 g NaOH as precipitants, and the obtained catalyst was recorded as C3Z1AG. The other preparation and evaluation steps were the same as those in Example 1.

[0056] Example 7

[0057] The metal salts used in the catalyst preparation were 6.084 g Cu(NO3)2·3H2O, 2.092 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, and 0.615 g Ga(NO3)2·3H2O. The precipitants used were 0.726 g Na2CO3 and 3.792 g NaOH. The obtained catalyst was recorded as C 3.5 Z1AG. Other preparation and evaluation steps are the same as those in Example 1.

[0058] Example 8

[0059] The metal salts used in the catalyst preparation were 6.258 g Cu(NO3)2·3H2O, 1.883 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, 0.615 g Ga(NO3)2·3H2O, 0.726 g Na2CO3 and 3.794 g NaOH as precipitants, and the obtained catalyst was recorded as C4Z1AG. The other preparation and evaluation steps were the same as those in Example 1.

[0060] Example 9

[0061] The metal salts used in the catalyst preparation were 6.519 g Cu(NO3)2·3H2O, 1.569 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, 0.615 g Ga(NO3)2·3H2O, 0.726 g Na2CO3 and 3.796 g NaOH as precipitants, and the obtained catalyst was recorded as C5Z1AG. The other preparation and evaluation steps were the same as those in Example 1.

[0062] Examples 10-15 are preparations of CuZnAlGa catalysts with different Al2O3 / Ga2O3 ratios:

[0063] Example 10

[0064] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 3.010 g Al(NO3)3·9H2O, and 0.123 g Ga(NO3)2·3H2O, and the precipitants used were 0.897 g Na2CO3 and 3.790 g NaOH. The obtained catalyst was recorded as CZA9G1. The other preparation and evaluation steps were the same as those in Example 1.

[0065] Embodiment 11

[0066] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 2.676 g Al(NO3)3·9H2O, 0.246 g Ga(NO3)2·3H2O, 0.8545 g Na2CO3 and 3.790 g NaOH, and the obtained catalyst was recorded as CZA8G2. The other preparation and evaluation steps were the same as those in Example 1.

[0067] Example 12

[0068] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 2.341 g Al(NO3)3·9H2O, 0.369 g Ga(NO3)2·3H2O, 0.812 g Na2CO3 and 3.790 g NaOH, and the obtained catalyst was recorded as CZA7G3. The other preparation and evaluation steps were the same as those in Example 1.

[0069] Embodiment 13

[0070] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 2.007 g Al(NO3)3·9H2O, 0.492 g Ga(NO3)2·3H2O, 0.769 g Na2CO3 and 3.790 g NaOH, and the obtained catalyst was recorded as CZA6G4. The other preparation and evaluation steps were the same as those in Example 1.

[0071] Embodiment 14

[0072] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 1.672 g Al(NO3)3·9H2O, 0.615 g Ga(NO3)2·3H2O, 0.726 g Na2CO3 and 3.790 g NaOH, and the obtained catalyst was recorded as CZA5G5. The other preparation and evaluation steps were the same as those in Example 1.

[0073] Embodiment 15

[0074] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 1.338 g Al(NO3)3·9H2O, 0.738 g Ga(NO3)2·3H2O, 0.683 g Na2CO3 and 3.790 g NaOH, and the obtained catalyst was recorded as CZA4G6. The other preparation and evaluation steps were the same as those in Example 1.

[0075] Example 16 is a comparative sample Cu / ZnO / Al2O3 hydrotalcite-derived catalyst

[0076] The metal salt used in the catalyst preparation was 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, 3.345 g Al(NO3)3·9H2O, and the precipitant used was 0.941 g Na2CO3 and 3.790 g NaOH. The obtained catalyst was recorded as CZA. The other preparation and evaluation steps were the same as those in Example 1.

[0077] Example 17 is a comparative sample Cu / ZnO / Ga2O3 hydrotalcite-derived catalyst

[0078] The metal salts used in the catalyst preparation were 5.867 g Cu(NO3)2·3H2O, 2.354 g Zn(NO3)2·6H2O, and 0.738 g Ga(NO3)2·3H2O, and the precipitants used were 0.683 g Na2CO3 and 3.790 g NaOH. The obtained catalyst was recorded as CZG. The other preparation and evaluation steps were the same as those in Example 1.

[0079] The XRD spectra of the catalyst precursors obtained in Comparative Examples 1-3 are shown in the attached Figure 1 As shown in Figure 2, all samples have characteristic diffraction peak structures of hydrotalcite-like structures in their XRD spectra. The sample (CZAG-LDH-EM) prepared by using a mixture of methanol and ethylene glycol as auxiliary solvents has the highest crystallinity. Figure 2 ) It can also be found that the sample prepared with the aid of methanol and ethylene glycol has the most uniform particle dispersion and the smallest particles, followed by the methanol-assisted preparation, and finally the catalyst prepared with the aid of ethylene glycol. This is mainly because the added ethylene glycol solution provides more hydroxide ions, which is more conducive to the formation of hydrotalcite-like structures. At the same time, the surface tension of the methanol solution is small, which is conducive to the dispersion of particles in the sample and the control of particle size.

[0080] The XRD spectra of the catalyst precursors obtained in Comparative Examples 4-9 and the samples after calcination and reduction are shown in the attached Figure 5 The precursors of all samples showed a hydrotalcite-like structure as shown in the attached Figure 5 In (a), different CuO / ZnO has a weak effect on the crystallinity of hydrotalcite-like materials. After calcination, the samples all show an amorphous phase as shown in the attached figure. Figure 5 (b) After the sample was reduced, the hydrotalcite-like structure collapsed completely, showing the characteristic peaks of CuO and ZnO as shown in the attached figure. Figure 5 (c) in the figure, and through the Scherrer formula, it is concluded that the Cu particles in the sample will slightly increase with the increase of Cu components.

[0081] The XRD spectra of the catalyst precursors obtained in Comparative Examples 10-17 and the samples after calcination and reduction are shown in the attached Figure 6As shown. Except for CZG, all samples behaved in the same manner as in Examples 4-9. The ratio of divalent metal ions to trivalent metal ions in the CZG precursor deviated from the ratio required for a complete hydrotalcite-like structure, resulting in a decrease in its crystallinity. The structure collapsed more easily after calcination and reduction, and the Cu particles grew significantly after reduction, as shown in the attached figure. Figure 6 (c) in .

[0082] The catalysts obtained in Examples 1-17 were used in the methanol production reaction of carbon dioxide-rich synthesis gas, and their catalytic activities were compared. The test results are shown in the attached Figure 3 , Attachment Figure 7 , Attachment Figure 8 .

[0083] The catalytic performance of CZAG hydrotalcite-derived catalysts prepared with the aid of different alcohol solutions is compared. The test results are shown in the attached Figure 3 Under the same conditions at 240 °C, CZAG-EM prepared with the assistance of methanol and ethylene glycol showed better catalytic activity than CZAG-M prepared with the assistance of methanol alone and CZAG-E prepared with ethylene glycol alone.

[0084] The catalytic performance of CuZnAlGa hydrotalcite-derived catalysts with different CuO / ZnO ratios is compared. The test results are shown in the attached Figure 7 The conversion rate of CO2 is Figure 7 The conversion rate of (a) and CO is as follows Figure 7 (b) and the methanol space-time yield STY are as follows Figure 7 (c) in Figure 1 all show a trend of first increasing and then decreasing with the increase of CuO / ZnO ratio. At the same time, it can be seen that all catalytic activities are affected by temperature in the same way. In the temperature range of 200-260℃, they show a trend of first increasing and then decreasing, and the best catalytic activity is shown at 240℃.

[0085] The catalytic performance of CuZnAlGa hydrotalcite-derived catalysts with different Al2O3 / Ga2O3 ratios is compared. The test results are shown in the attached Figure 5 The conversion rate of CO2 is Figure 8 The conversion rate of (a) and CO is as follows Figure 8 (b) and the methanol space-time yield STY are as follows Figure 8 Most of the (c) in the figure show a trend of increasing first and then decreasing with the increase of Al2O3 / Ga2O3 ratio. The CO conversion rate of some catalysts may be slightly deviated due to the influence of catalyst structure. At the same time, it can be seen that all catalytic activities are affected by temperature in the same way. In the temperature range of 200-260℃, they show a trend of increasing first and then decreasing, and the best catalytic activity is shown at 240℃.

[0086] In order to explore the effect of Ga element on catalytic performance, the present invention compared the catalytic activities of three hydrotalcite-derived catalysts CZA, CZAG and CZG obtained in Examples 14, 16 and 17. The test results are shown in the attached figure. Fig. 9 As shown in the figure. After the introduction of Ga into CZA, the CO2 conversion rate and CO conversion rate are significantly improved. This is because the introduction of Ga and the Cu site synergistically form more active centers. According to the XRD spectrum and Scherrer formula calculation, it can be found that the introduction of Ga also reduces the size of Cu particles. Figure 6 (c) in the figure enhances the interaction between Cu and ZnO and increases the density of active sites. Under the synergistic effect of Cu-Ga2O3 and Cu-ZnO, the non-competitive adsorption of CO molecules and CO2 molecules is promoted, effectively improving the catalytic activity. In the CZG catalyst, we can find that due to the absence of Al, on the one hand, the inappropriate metal ratio leads to an incomplete hydrotalcite-like structure, and on the other hand, there is no Al2O3 as a structural additive. After calcination and reduction of the CZG sample, the Cu particles aggregate, resulting in a decrease in the density of active centers, which affects the conversion rate of CO and CO2 and the yield of methanol. Under the same reaction conditions, the STY of the CZA catalyst is MeOH 413g kg -1 cat h -1 , STY of CZAG catalyst MeOH 517g kg -1 cat h -1 , STY of CZAG catalyst MeOH 467g kg -1 cat h -1 .

[0087] Long-term stability evaluation results of the CuZnAlGa hydrotalcite-derived catalyst prepared in Example 14 at a reaction temperature of 240°C (see Appendix Fig.10 ) shows that the CO2 conversion rate is always maintained at about 18.5% within the reaction time of 100h, the CO conversion rate is maintained at about 44%, and the space-time yield of CH3OH is stable at 510g MeOH Kg -1 Cat h -1 This indicates that the CuZnAlGa-type hydrotalcite-derived catalyst has good stability.

[0088] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a CuZnAlGa-based hydrotalcite-derived catalyst for preparing methanol from carbon dioxide-rich synthesis gas, characterized in that: The following steps are involved: 1) Co-precipitation: weigh a certain mass of Cu salt, Zn salt, Al salt, and Ga salt and dissolve them in a mixed alcohol aqueous solution; weigh a certain amount of precipitant and dissolve it in the mixed alcohol aqueous solution; drip the two solutions dropwise into a container simultaneously; during the process, the mixture is heated at a constant temperature of 30-60° C. and stirred; and the pH value is controlled at 8-10; continue stirring for 6-18 hours under the hydrothermal condition, stop stirring, and cool to room temperature; the mixed alcohol in the mixed alcohol aqueous solution is two or more of methanol, ethanol, n-propanol, n-butanol, ethylene glycol, and glycerol; 2) separation: the precipitate of step 1) is separated by suction filtration, and the filter cake is washed with water and ethanol for multiple times to obtain a light blue precipitate in a colloidal state; 3) Drying: Dry the light blue precipitate from step 2) in an oven; 4) High temperature calcination: grind the light blue solid dried in step 3) and calcine at 320-500° C. for 4-6 hours; 5) Activation: Reduce the CuZnAlGa hydrotalcite-derived catalyst obtained in step 4) at 250-300° C. in a reducing gas atmosphere for 1-4 h to obtain a CuZnAlGa catalyst with multiple active centers, which is composed of metal Cu nanoparticles and ZnO, Al2O3, and Ga2O3 metal oxides, maintains a layered skeleton structure, and has multiple active sites, wherein the mass ratio of (CuO+ZnO) to (Al2O3+Ga2O3) is (5-9):1, the mass ratio of CuO to ZnO is (2-5):1, and the mass ratio of Al2O3 to Ga2O3 is (1-9):

1.

2. The method for preparing the catalyst according to claim 1, characterized in that: In step 1), the Cu salt, Zn salt, Al salt and Ga salt are one or more of nitrate, acetate, halide and sulfate.

3. The method for preparing the catalyst according to claim 1, characterized in that: The precipitant is one or more than two of sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide and potassium hydroxide.

4. The method for preparing the catalyst according to claim 1, characterized in that: In step 1), the mixed alcohol in the mixed alcohol aqueous solution is methanol and ethylene glycol, and the volume concentration of the mixed alcohol aqueous solution is 5-40%.

5. The method for preparing the catalyst according to claim 1, characterized in that: The prepared catalyst is used to produce methanol from carbon dioxide-rich synthesis gas at a reaction pressure of 3-7 MPa, a reaction temperature of 180-280°C, and a reaction gas space velocity of 3000-18000 mL / (g cat h), the raw gas is carbon-rich synthesis gas with a CO2 content of 20%.

Citation Information

Patent Citations

  • Catalyst for preparing methanol from carbon dioxide-rich synthesis gas as well as preparation method and application of catalyst

    CN116273013A

  • Methanol synthesis catalyst

    JP1997141100A

  • Catalyst for synthesizing methanol

    JP1997267041A

  • Cu-Zn-Al based catalyst for methanol synthesis and its preparation method via alcohol

    KR1020170006664A

  • Process for manufacturing catalysts containing copper, zinc and aluminum, useful for producing methanol from synthesis gas

    US4596782A

Cited By

  • Doped Cu-based catalyst, preparation method and application of doped Cu-based catalyst in ethanol synthesis

    CN120381880A

  • Doped Cu-based catalyst, preparation method and application thereof in ethanol synthesis

    CN120381880B

  • Sulfur gallium zinc copper / titanium dioxide composite photocatalyst as well as preparation method and application thereof

    CN120618490A

  • Copper-based catalyst for synthesizing methanol as well as preparation method and application of copper-based catalyst

    CN121338755A

  • Catalyst for preparing methanol from CO2-rich synthesis gas as well as preparation method and application of catalyst

    CN121669299A